2003
DOI: 10.1002/glia.10278
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of astrocyte connexins Cx26, Cx30, Cx43 to oligodendrocyte Cx29, Cx32, Cx47: Implications from normal and connexin32 knockout mice

Abstract: Oligodendrocytes in vivo form heterologous gap junctions with astrocytes. These oligodendrocyte/ astrocyte (A/O) gap junctions contain multiple connexins (Cx), including Cx26, Cx30, and Cx43 on the astrocyte side, and Cx32, Cx29, and Cx47 on the oligodendrocyte side. We investigated connexin associations at A/O gap junctions on oligodendrocytes in normal and Cx32 knockout (KO) mice. Immunoblotting and immunolabeling by several different antibodies indicated the presence of Cx32 in liver and brain of normal mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
188
0
7

Year Published

2003
2003
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(216 citation statements)
references
References 49 publications
21
188
0
7
Order By: Relevance
“…We show that neuronal gap junctions in SCN were present in two major classes -a few large "conventional" gap junctions vs. more abundant miniature ("mini") gap junctions, most of which were smaller than 50 connexons. Our data also support the hypothesis of cell-type-specific expression of the other three connexins tested, with Cx32 confined to oligodendrocyte gap junctions; Cx30 and Cx43 in astrocyte gap junctions; and Cx43 (but none of the other connexins) in ependymocyte junctions, extending similar data from other regions of the CNS (Rash et al, 2001a(Rash et al, , 2001bNagy et al, 2003aNagy et al, ., 2003bNagy et al, , 2004Kamasawa et al, 2005Kamasawa et al, , 2006. The physiological data in the current study also demonstrate that the proportion of cell pairs that show evidence for electrotonic or tracer coupling or spike-to-spike synchrony is quite low (i.e., no spike synchrony in our study and only one pair of tracer-coupled neurons).…”
supporting
confidence: 89%
See 1 more Smart Citation
“…We show that neuronal gap junctions in SCN were present in two major classes -a few large "conventional" gap junctions vs. more abundant miniature ("mini") gap junctions, most of which were smaller than 50 connexons. Our data also support the hypothesis of cell-type-specific expression of the other three connexins tested, with Cx32 confined to oligodendrocyte gap junctions; Cx30 and Cx43 in astrocyte gap junctions; and Cx43 (but none of the other connexins) in ependymocyte junctions, extending similar data from other regions of the CNS (Rash et al, 2001a(Rash et al, , 2001bNagy et al, 2003aNagy et al, ., 2003bNagy et al, , 2004Kamasawa et al, 2005Kamasawa et al, , 2006. The physiological data in the current study also demonstrate that the proportion of cell pairs that show evidence for electrotonic or tracer coupling or spike-to-spike synchrony is quite low (i.e., no spike synchrony in our study and only one pair of tracer-coupled neurons).…”
supporting
confidence: 89%
“…6C,D; paranodal loops are numbered 1-4), and on the outer surface of myelin (Fig. 6E) Nagy et al, 2003aNagy et al, , 2003bNagy et al, , 2004. In high-magnification stereoscopic views (Fig.…”
mentioning
confidence: 99%
“…Cx43/Cx47 and Cx30/Cx32 likely form two parallel sets of heterotypic channels that constitute A/O coupling. These two pairs of connexins colocalize at A/O gap junction plaques in WT brains, but Cx30 (and not Cx43) is mislocalized in Gjb1/cx32-null brains (Nagy et al 2003;Altevogt and Paul 2004). Cx30 and Cx32 can form functional heterotypic channels in oocytes (Dahl et al 1996), but it remains to be shown whether Cx43 and Cx47 can also form functional heterotypic channels.…”
Section: Cx47 Mutants Affect the Panglial Syncytiummentioning
confidence: 97%
“…Astrocyte/astrocyte (A/ A) coupling is likely mediated by Cx43/Cx43 and Cx30/Cx30 homotypic channels, and astrocyte/oligodendrocyte (A/O) coupling is most likely mediated by Cx43/Cx47 and Cx30/ Cx32 heterotypic channels, with an uncertain contribution of Cx26/Cx32 channels (Rash et al 2001;Nagy et al 2003;Altevogt and Paul 2004;Li et al 2004). Cx32/Cx32 homotypic channels appear to form gap junctions between layers of CNS myelin sheaths (Kamasawa et al 2005), as previously described in PNS myelin sheaths (Bergoffen et al 1993;Scherer et al 1995;Balice-Gordon et al 1998;Meier et al 2004).…”
mentioning
confidence: 99%
“…Gap junction channels are formed by the joining of two hemichannels (connexons) between adjacent cells each composed of hexameric protein subunits called connexins (Cx). Several connexins have been reported to be expressed by astrocytes including connexin 43 (Cx43), connexin 26 (Cx26), and connexin 30 (Cx30) (Altevogt and Paul, 2004;Dermietzel et al, 2000;Nagy et al, 2001Nagy et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%